Legal Review of the Application of Administrative Sanctions in Tax Regulations in Indonesia - Ahmad Vickry; Ash Shaff Rhohim; Muhammad Daffa Thariq; Munawati Ritonga; Nazwa Dwi Harika (Jurnal Cendikia ISNU SU, 2025)
Administrative sanctions in tax law are an important instrument in disciplining taxpayers and maintaining tax administrative order in Indonesia. This article aims to analyze juridically the legal basis, form, and effectiveness of the application of administrative sanctions in the national tax system. With a normative juridical approach, this study examines the provisions of laws and regulations, especially the Law on General Provisions and Tax Procedures (UU KUP) and its latest amendments through the Law on Harmonization of Tax Regulations (UU HPP). The results of the study show that the implementation of administrative sanctions has contributed to increasing taxpayer compliance, but it has also raised debates in terms of fairness and proportionality. Therefore, it is necessary to reformulate the tax law enforcement approach to be more fair and responsive to the context of the violations that occur.